Exploring Social Sustainability and Economic Practices (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Given the three pillars of sustainability, besides the environment, the interplay of social and economic dimensions provides valuable insight into how society is molded and the key components that should be considere. In terms of social sustainability, processes and framework objectives promote the wellbeing that is integral to the balance of people, planet, and profit. Economic practices consider the system of production, resource allocation, and distribution of goods and services with respect to demand and supply between economic agents. As a result, an economic system is a variant of the social system in which it exists. At present, the forefront of social sustainability research partially encompasses the impact of economic practices on people and society, with notable emphasis centered on the urban environment. Specific interdisciplinary analyses within the scope of sustainability, social development, competitiveness, and motivational management, as well as decision making within the urban landscape, are considered. This book contains nine thoroughly refereed contributions that interconnect detailed research into the two pillars reviewed.